1997
DOI: 10.1046/j.1365-2567.1997.d01-2148.x
|View full text |Cite
|
Sign up to set email alerts
|

A comparative study of the in vitro immunomodulatory activity of human intact immunoglobulin (7S IVIG), F(ab′)2 fragments (5S IVIG) and Fc fragments. Evidence for post‐transcriptional IL‐2 modulation

Abstract: We demonstrate that mainly 7S IVIG inhibits alloantigen-induced T-cell proliferation and generation of cytotoxic T lymphocytes. Reduced interleukin-2 (IL-2 ) protein levels in culture supernatants of IVIG-supplemented mixed lymphocyte reactions (MLR) but unchanged IL-2 mRNA levels strongly argue in favour of a post-transcriptional interference of IVIG with cytokines and/or cytokine production. Interferon-c ( IFN-c), soluble IL-2 receptor (sIL-2R) and monokines such as IL-1b, IL-6, IFN-a and tumour necrosis fac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
26
0
1

Year Published

1999
1999
2012
2012

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(29 citation statements)
references
References 29 publications
2
26
0
1
Order By: Relevance
“…16 Larger studies have not been carried out with this agent. In view of studies by Nachbaur et al 19,20 on the in vitro immuno-modulatory activity of immunoglobulins it appears likely that this might be the mechanism by which an anti GVHD effect can be achieved. Using Pentaglobin the authors demonstrated that proliferation in the mixed-lymphocyte reaction was highly suppressed by IgMcontaining Pentaglobin fractions.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…16 Larger studies have not been carried out with this agent. In view of studies by Nachbaur et al 19,20 on the in vitro immuno-modulatory activity of immunoglobulins it appears likely that this might be the mechanism by which an anti GVHD effect can be achieved. Using Pentaglobin the authors demonstrated that proliferation in the mixed-lymphocyte reaction was highly suppressed by IgMcontaining Pentaglobin fractions.…”
Section: Discussionmentioning
confidence: 99%
“…Cytokine analysis and culture supernatants provide evidence that Pentaglobin leads to a down regulation of interleukin-2, interferon-␥, and monocyte-derived tumornecrosis factor ␣, as well as interleukin-6 release. 19,20 In summary, five-agent GVHD prophylaxis with cyclosporine, methotrexate, anti-thymocyte-globulin, Pentaglobin and metronidazol is an effective regimen. Whether all five components are essential for this effect cannot be stated with certainty.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are several reports of the effects of IVIg on cytokine production by human PBMCs. With respect to cytokine production induced by a mixed lymphocyte reaction (MLR), the productions of interleukin (IL)-2, interferon (IFN)-, TNF-, and IL-6 were inhibited by IVIg [21], and the inhibitory action of IVIg on IL-2 production was stronger than that of F(ab') 2 [22]. With respect to cytokine production induced by LPS, the production of IL-6, TNF-, and IL-8 was inhibited [18,23,24], supporting the results shown in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have shown that high IVIG concentrations inhibit lymphocyte proliferation in the presence of various stimulants irrespective of the cell types including several malignant cell lines (16), and of the IVIG preparations (whole IgG, F(ab′ )2 fragment (17,20), Fc fragments (15,20), or repurified IVIG (17), IgG from single or five donors (17)). …”
Section: Discussionmentioning
confidence: 99%